GREEN FINANCE AND CASH MANAGEMENT: AN INNOVATIVE ALLIANCE FOR A PROSPEROUS AND SUSTAINABLE FUTURE IN AFRICA - (:unkn) unknown (My University, 2023)
In a turbulent and globalised environment, the survival of companies and the achievement of sustainable development objectives are drawing the international community's attention. At the continental level, businesses represent the backbone of the African economy and its social and economic security valve. In parallel, cash management that combines efficiency and innovation is the cornerstone for driving performance and strengthening growth. The health, environmental and financial crises that have shaken markets and disrupted economies are a reminder of this reality. Thus, at a time of environmental challenges and unbridled changes in the financial ecosystem towards globalisation, cash management function is invited to put financial performance and sustainable development on the same table. To meet these prerogatives, cash managers are now called upon to modify their management DNA towards innovative practices by fully exploiting the potential of green finance. In this regard, they can explore new alternative sources of financing, take advantage of revolutionary IA technology, or invest in green bonds to support projects with a strong environmental and social impact while benefiting from a significant financial return. In this respect, the results of the present chapter show that green finance promises to be a key driver of performance and growth which should soon be making inroads into cash management function of African companies in order to strengthen their resilience in the face of potential challenges. In addition, green digital finance is proving to be a catalyst for promoting financial inclusion and accelerating the achievement of sustainable development goals. Moreover, embracing green finance services gives companies a competitive edge, enhancing therefore their position on the international economic podium.
Keywords: African Research